Effect of message congruency on attention and recall in pictorial health warning labels. Issue 3 (16th May 2017) - Lochbuehler, Kirsten; Mercincavage, Melissa; Tang, Kathy Z; Dana Tomlin, C; Cappella, Joseph N; Strasser, Andrew A
Abstract : Objective: The nine pictorial health warning labels (PWLs) proposed by the US Food and Drug Administration vary in format and feature of visual and textual information. Congruency is the degree to which visual and textual features reflect a common theme. This characteristic can affect attention and recall of label content. This study investigates the effect of congruency in PWLs on smoker's attention and recall of label content. Methods: 120 daily smokers were randomly assigned to view either congruent or incongruent PWLs, while having their eye movements recorded. Participants were asked to recall label content immediately after exposure and 5 days later. Results: Overall, the image was viewed more and recalled better than the text. Smokers in the incongruent condition spent more time focusing on the text than smokers in the congruent condition (p=0.03), but dwell time of the image did not differ. Despite lower dwell time on the text, smokers in the congruent condition were more likely to correctly recall it on day 1 (p=0.02) and the risk message of the PWLs on both day 1 (p=0.01) and day 5 (p=0.006) than smokers in the incongruent condition. Conclusions: This study identifies an important design feature of PWLs and demonstrates objective differences in how smokers process PWLs. Our results suggest that message congruency between visual and textual information is beneficial to recall of label content. Moreover, images captured and held smokers' attention better than the text.